Morphological variability within the Achnanthidium minutissimum species complex (Bacillariophyta): comparison between the type material of Achnanthes minutissima and related taxa, and new freshwater Achnanthidium species from Portugal - Novais, Maria Helena; Jüttner, Ingrid; Vijver, Bart Van De; Morais, Maria Manuela; Hoffmann, Lucien; Ector, Luc (Phytotaxa, 2015)
Two new taxa similar to Achnanthidium minutissimum were common and abundant in samples collected during a survey of benthic diatoms in watercourses from mainland Portugal. They are described here as A. duriense, sp. nov. and A. lusitanicum, sp. nov. In addition, the recently described A. pseudolineare is reported from various localities and its ecology is described in detail. The new Achnanthidium species from Portugal were compared with the type material of morphologically similar taxa: Achnanthidium microcephalum, Achnanthes minutissima, A. minutissima var. cryptocephala, A. minutissima var. inconspicua and A. nana. The analysis of this type material confirmed that Achnanthes minutissima var. cryptocephala should be regarded as a different taxon, and a new combination is proposed, Achnanthidium neocryptocephalum, stat., comb. et nom. nov. Achnanthes minutissima var. inconspicua is now considered as a younger synonym of Achnanthidium lineare. Based on a detailed morphological study of specimens of Achnanthes nana from Scotland, Nepal and Portugal, this taxon is transferred to the genus Achnanthidium as Achnanthidium nanum, comb. nov.